Lessons from the contrast dye shortage during COVID-19: A narrative review. Issue 51 (23rd December 2022) - Yu, Christiaan
Abstract : The sudden contrast dye shortage, precipitated by a temporary forced closure of healthcare plant, has limited the supply of iodinated contrast media to Australia. Furthering the impact of the coronavirus disease 2019 pandemic, this new crisis has increased burden on the radiology system. Lessons from the strategies applied during the shortage should be used as building blocks as safeguards for the future. A pragmatic approach to education and training is required in an ever-changing environment. Our relationships between medical specialties and manufacturers are paramount to maintaining an effective workflow. An ongoing commitment to a strong workforce will be the backbone to overcome another challenge in these uncertain times.